KONSEP KEADILAN DALAM POLIGAMI MENURUT AGAMA ISLAM - Sayyidah, Sayyidah; Rahman, Imas Kania; Ramly, Amir Tengku (Diversity: Jurnal Ilmiah Pascasarjana, 2021)
This article focuses on the discussion of the Kagian Islam on justice in polygamy, namely; what are the requirements for polygamy according to the priests of the mazhab, how the arguments and laws of the priests of the mazhab allow polygamy, and how is it relevant to polygamy according to the contemporary context in Indonesia. This research is a library research (Library Reserach), which is a method of collecting data such as the books of the priests of the mazhab and books that are relevant to the issues discussed. This research is a descriptive analysis, which describes, studies and analyzes the opinions of the Imam of the Schools in terms of being fair in polygamy. The results showed that in Islam it is permissible for a husband to practice polygamy on the condition that he believes or has a strong suspicion that he is able to do justice to his wives. as indicated by the al-Qur'an in the letter al-Nisa "verse 3:" then if you are afraid that you will not be able to act fairly, then marry only one wife ". This permissibility for polygamy is not a recommendation but one of the solutions given in special conditions to those (husbands) who really need and fulfill certain conditions. The meaning of justice as a condition for polygamy is not in the inner meaning of justice (such as love and affection) but justice for things that are material and measurable. As indicated by verse 129 of the letter al-Nisa 'and the sociological background because of the verse polygamy (verse 3 al-Nisa'). What is meant by the fairest distribution is in terms of: income, clothing, place to live, and time of turn